A Beginning Teacher's Guide to Special Education Needs - Wearmouth Janice (Mcgraw Hill, 2009)
This book provides an excellent intoduction and practice in Special Educational Needs. Preface, Special Educational Needs: Policy and Context, Making Sense of Learning and Difficulties in Learning, A Historical Perspective and the Current Legal Position, Approaches to Assessment and Planning and Teaching and Learning, Overview of Approaches to Four Areas of Need, Assessment and Planning, Addressing the Needs of Learners who Experience Literacy Difficulties, Understanding and Addressing Special Difficulties in Mathematics, Behavioural Issues in Classrooms, Support for Special Learning Needs, Uses of ICT to Support Students' Special Learning Needs, Professional Relationships with Other People, Final Word, References, Index.